1992
DOI: 10.1016/0304-3959(92)90099-w
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pain sensitivity and blood pressure in normotensives

Abstract: Hypertension has been found to be related to decreased sensitivity to painful stimuli. The current study explored whether this relationship extends into the normotensive range of blood pressures. Resting blood pressures were assessed in 60 male normotensives. Subjects then underwent a 1 min finger pressure pain stimulation trial. Pain ratings were inversely related to resting systolic blood pressure. This relationship was unrelated to emotional state or coping styles. Multiple regression analyses indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
2
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(118 citation statements)
references
References 17 publications
5
110
2
1
Order By: Relevance
“…They found a generally higher pain tolerance in the borderline hypertensive subjects as compared to the normotensive ones. Similarly, Bruehl et al (1992) found subjective pain ratings were significantly correlated (r= −0.43) with resting systolic, but not diastolic (r = −0.11) blood pressure. Subjects with higher, but still normotensive, blood pressure values reported less pain during this mechanical pain maneuver.…”
Section: Relationship Between Tonic Blood Pressure Le6el and Pain Senmentioning
confidence: 76%
“…They found a generally higher pain tolerance in the borderline hypertensive subjects as compared to the normotensive ones. Similarly, Bruehl et al (1992) found subjective pain ratings were significantly correlated (r= −0.43) with resting systolic, but not diastolic (r = −0.11) blood pressure. Subjects with higher, but still normotensive, blood pressure values reported less pain during this mechanical pain maneuver.…”
Section: Relationship Between Tonic Blood Pressure Le6el and Pain Senmentioning
confidence: 76%
“…The hyperalgesic effects of this profile can be interpreted in light of literature regarding blood pressure-related analgesia. Elevated resting blood pressure is reliably associated with reduced acute pain responsiveness (Bruehl et al 1992;Ghione 1996), and evidence suggests that transient increases in systolic blood pressure also elicit hypoalgesia (Edwards et al 2001;. Individuals who are prone to catastrophize about pain who also exhibit low stress-induced cardiovascular reactivity may experience greater daily chronic pain intensity due to automatic negative appraisals of pain stimuli in combination with limited activation of blood pressure-related antinociceptive mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A negative relationship between tonic blood pressure and pain sensitivity has been repeatedly observed in humans (Bruehl, Carlson & McCubbin, 1992;Ghione, Rosa, Mezzasalma & Panattoni, 1988;Ghione, Rosa, Panattoni, Nuti, Mezzasalma & Giuliano, 1985;Maixner, 1991;Zamir & Shuber, 1980) and animals (Maixner, Touw, Brody, Gebhart & Long, 1982). One link between the cardiovascular system and the central nervous system is the arterial baroreceptors which serve as sensors for blood pressure and its changes and which are involved in cardiovascular homeostasis (Persson & Kirchheim, 1991).…”
Section: Introductionmentioning
confidence: 91%